Women’s Participation In Badminton Sports In Medan City In 2025 - Irfan, Mhd.; Ramadhan, M.Elza Fahlevi; Fahreza, Mhd. Rizky (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research uses descriptive method and data collection through Google Form questionnaire. Therefore, descriptive statistical techniques with percentages were applied to find out how the factors that influence women to participate in badminton sports in Medan City. Descriptive research focuses on presenting and explaining data in narrative form, while quantitative research involves analyzing data numerically to describe it. In accordance with the title that has been raised, namely Female Participants in Badminton Sports in Medan City. The number of subjects in this study were 60 people. The results of the recapitulation calculation of the level of participation of women in badminton sports in Medan City in 2025 based on each factor of the level of sports participation. 1) Internal factors with a participation percentage of 69.8% and a recapitulation of 43.62%, 2). External factors with a participation percentage of 60.77% and a recapitulation result of 22.79%. It can be concluded that women's participation in badminton in Medan City in 2025 is more dominant due to internal factors than due to external factors.